2015
DOI: 10.1016/j.neuint.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

mGlu5-GABAB interplay in animal models of positive, negative and cognitive symptoms of schizophrenia

Abstract: Diverse preclinical studies exploiting the modulation of the GABAergic and/or glutamatergic system in brain via metabotropic receptors suggest their potential therapeutic utility. GS39783 and CDPPB, positive allosteric modulators of GABAB and mGlu5 receptors, were previously shown to reverse behavioral phenotypes in animal models to mimic selected (predominantly positive) symptoms of schizophrenia. In the present study we investigated the activity of selected GABAB (GS39783 and CGP7930) and mGlu5 (CDPPB) posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 71 publications
(104 reference statements)
1
32
1
Order By: Relevance
“…The GABAergic system plays an important role in the development of schizophrenia because according to the GABAergic theory of psychosis, the deficit in GABA synthesis was observed in postmortem studies of schizophrenic patients [ 41 ]. Our previous publications showed that GABA B receptor agonists/PAMs were effective in the animal models of positive symptoms [ 18 ] as well as in those of negative and cognitive symptoms [ 19 ]. We also showed that the concomitant stimulation of GABA B and mGlu 5 receptors with subeffective doses of selective PAMs of those receptors (GS39783 and CDPPB, respectively) induced clear antipsychotic-like effects in the animal models of schizophrenia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GABAergic system plays an important role in the development of schizophrenia because according to the GABAergic theory of psychosis, the deficit in GABA synthesis was observed in postmortem studies of schizophrenic patients [ 41 ]. Our previous publications showed that GABA B receptor agonists/PAMs were effective in the animal models of positive symptoms [ 18 ] as well as in those of negative and cognitive symptoms [ 19 ]. We also showed that the concomitant stimulation of GABA B and mGlu 5 receptors with subeffective doses of selective PAMs of those receptors (GS39783 and CDPPB, respectively) induced clear antipsychotic-like effects in the animal models of schizophrenia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous publications showed that GABA B receptor agonists/PAMs were effective in the animal models of positive symptoms [ 18 ] as well as in those of negative and cognitive symptoms [ 19 ]. We also showed that the concomitant stimulation of GABA B and mGlu 5 receptors with subeffective doses of selective PAMs of those receptors (GS39783 and CDPPB, respectively) induced clear antipsychotic-like effects in the animal models of schizophrenia [ 19 ]. This interplay between mGlu 5 and GABA B receptors was evident in the models of negative and cognitive symptoms, but not in the model of positive symptoms of schizophrenia, such as the DOI-induced head twitches [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified forced swim test was performed according to the method introduced by Noda ( Noda et al, 1995 , 1997 ; Wierońska et al, 2015a ; Woźniak et al, 2016a ). The swim tests were performed in a glass cylinder (height, 20 cm; internal diameter, 15 cm) containing 11 cm of water maintained at 23–24°C.…”
Section: Methodsmentioning
confidence: 99%
“…Together, these two neurotransmitters constitute more than 90% of all neurotransmission. If this homeostasis is disturbed it could lead to anxiety disorders (Wieronska et al, 2015).…”
Section: General Role In Biologymentioning
confidence: 99%